Tourism Marketing In Kerala: Perception-driven Strategies For Tourism Growth - P, Akhilasan; B, Kannan (South India Journal of Social Sciences, 2025)
The Indian tourist business has been expanding at a healthy clip over the last several years. With an average daily tariff of around 85 USD in 2016, hotels had their lowest performance in a decade. The occupancy rate of India’s hotel business has been stable at roughly 60% every year for the last many years, even though the average daily tariff has been declining. Traditional hotel room occupancy has been declining as non-traditional lodging options such as home stays, hostels, serviced flats, Airbnb, and OYO Rooms have emerged. When it comes to infrastructure, connectivity, and tourist safety, India’s travel and tourism sector is seeing a fresh wave of growth. Everything from a state or city to a specific historical monument, a hotel, a conference center, or any other kind of venue may be advertised as a tourist destination via tourism marketing. It cannot be restricted with particular aspects of travel and tourism.